Delimitation and characterization of alluvial fans in the bajada of Aguas Zarcas, Costa Rica - Mora Chinchilla, Rolando (2024)
Alluvial fans are sedimentary forms typical of mountainous regions, where the flow of water loaded with sediments comes out of narrow canyons to wider and lower slope areas, depositing the sediments and forming fan-shaped structures. These fans can vary in activity, with some being very dynamic with frequent flooding and others more stable due to the geological configuration and tectonic processes. In the Bajada de Aguas Zarcas, located in the Aguas Zarcas District, Canton of San Carlos, Alajuela, Costa Rica, several coalescent alluvial fans were identified. Among these, the Aguas Zarcas River fan is the most extensive, followed by others such as the Aguas Zarcas paleo-river, the San Rafael River, and the Negritos River, among others. The morphology of these fans shows that sediments accumulate and spread, creating characteristic landforms. The composition of the fans in Aguas Zarcas varies from blocks of centimeter to metric dimensions in the proximal areas, to sandy strata and ash in the distal areas. Identification of active and inactive areas of these fans is crucial for assessing flood risk. Active areas are those where deposition and erosion are possible, and may be more prone to future flooding. The study included the use of geological and topographic maps, as well as field inspections to verify the activity of the fans. It was determined that the alluvial fans in the Bajada de Aguas Zarcas have been influenced by tectonic and volcanic processes, affecting the deposition and flow of sediments. This analysis provides a basis for risk management and sustainable development in flood-prone areas, highlighting the importance of understanding the sedimentary and geomorphological dynamics of alluvial fans.